“Evaluacion de tres dosis de micromate calcium fortied en sistema de espaldera en el cultivo de pepino híbrido (cucumis sativus L.) -provincia de Lamas-región San Martín” - Dios Perez, Flavio Leonardo Fabian (2014)
This research paper entitled "Evaluation of three doses of Calcium Fortified Micromate in trellis system in the cultivation of hybrid cucumber (Cucumis sativus L.) - Province of Lamas - Region San Martin", aimed to: determine the optimal dose of Calcium Micromate Fortied (MCF) in the cultivation of gherkin using the 143 hybrid Hyb tournament. MoS F1 trellis system. This research was conducted in Fundo "THE PACIFIC" Lamas District, Province Lamas, San Martin Region Department. The Block Design was applied completely randomized (RCBD) with 5 treatments and 3 treatments were 25 kg I ha of MCF, 50 kg J ha of MCF, 75 kg J ha of MCF, 100 kg J ha of MCF and an Absolute control (no MCF). The obtained results indicate that the dose of 75 kg.ha-1 Calcium Micromate Fortied (MCF) it was the treatment that registers the major average of performance with 112.295,86 kg.ha-1 anda benefit cost of 2,75. Keywords: trellis system, cucumber cultivation, yield, fruit weight.